Síntomas gripales asociados a la vacunación antigripal en personal de salud - Sammartino, Inés; Torlaschi, Ana Laura; Schang, María Victoria; Silveira, Martín; Andrés, Ingrid; Garfi, Leonardo; Giunta, Diego; Clara, Liliana; González Bernaldo de Quirós, Fernán (Revista del Hospital Italiano de Buenos Aires, 2009)
Introduction: In May 2009, prior to the beginning of winter in the Southern hemisphere, a massive vaccination campaign for the personnel was performed at the Hospital Italiano de Buenos Aires. Objective: To assess symptoms associated with influenza vaccination in health personnel. Methods: In a cohort study, the impact of flu symptoms reported for the epidemiological week number 20 were compared using the relative risk between 400 vaccinated vs. 400 unvaccinated individuals matched for age, sex and occupation. Symptoms reported within 48 hours after vaccination were considered secondary this event. Results: 583 people were respondents (72.5%) of whom 281 were vaccinated vs. 302 who were unvaccinated (mean age, 36 yr (SD 11 yr) vs. 35.2 yr (SD 10.5 yr); women, 54% vs. 57%; doctors 21% vs. 18%, respectively). During the vaccination week, 12.46% vaccinated vs. 6.95% unvaccinated individuals presented fever (RR 1.79, CI95% 1.07-3); a cold, 24.2% vs. 17.2% (RR 1.41, CI95% 1.02-1.94); sore throat, 11.74% vs. 0.33% (RR 35.47, CI 95% 4.88-257); body pain, 18.86% vs. 14.57% (RR 1.29, CI 95% 0.9-1.87), respectively. Symptoms attributed to the vaccine were: body pain, 9.25% (CI95% 6.3-13.6); cold, 8.19% (CI95% 5.4-12.31); fever, 6.78% (CI95% 4.31-10.6); sore throat, 4.27% (CI 95% 2.42-7.5); and arm pain, 65%. Doctors did not report a higher frequency of flu symptoms. Discussion: Sore throat and cold are not symptoms commonly reported in association with vaccination. The frequency of other symptoms following the first 48 hours of vaccination was similar to previous reports. Conclusion: The flu syndrome was reported more frequently in vaccinated people as compared with those unvaccinated. However, these results might be due to a reporting
Keywords: flu vaccination; health personnel; flu like symptoms